2011
DOI: 10.2352/j.imagingsci.technol.2011.55.4.040301
|View full text |Cite
|
Sign up to set email alerts
|

Ink Jet Technology for Large Area Organic Light-Emitting Diode and Organic Photovoltaic Applications

Abstract: Due to its flexibility and ease of patterning, ink jet printing has become a popular technique for the noncontact deposition of liquids, solutions, and melts on a variety of substrates at lateral resolutions down to 10 lm. This article presents a study of ink jet printing of homogeneous layers of Orgacon TM (Agfa-Gevaert, Belgium), a water-based dispersion of poly(3,4-ethylenedioxythiophene):poly (styrenesulfonic acid) (PEDOT:PSS). The printed PEDOT:PSS layer can be used as a transparent electrode in organic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Figures 1b and 2 imply that elastic responses of the PEDOT:PSS solutions can not significantly contribute to the satellite production. As surfactants take time (typically > 10 -2 s for dynamic surface tension lowering [4]) to reach fresh surfaces, ink-jet satellite production should be enhanced for all of the aqueous solutions. However the major difference here between shear thinning ( Figure 1a) and Newtonian fluids in terms of satellite formation could be due to a difference in their viscosity at the low shear rates relevant to fluid motion in the ligament.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 1b and 2 imply that elastic responses of the PEDOT:PSS solutions can not significantly contribute to the satellite production. As surfactants take time (typically > 10 -2 s for dynamic surface tension lowering [4]) to reach fresh surfaces, ink-jet satellite production should be enhanced for all of the aqueous solutions. However the major difference here between shear thinning ( Figure 1a) and Newtonian fluids in terms of satellite formation could be due to a difference in their viscosity at the low shear rates relevant to fluid motion in the ligament.…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous dispersions of PEDOT:PSS with or without surfactants have been successfully deposited by inkjet printing for some years to form transparent conductors in printed electronics [1][2][3][4][5][6][7][8], but it has only recently become apparent that their main and satellite drop formation across a wide range of speeds is unusual in comparison with most other printable polymeric fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Inks of this polyelectrolyte system have been prepared and processed by using inkjet for the manufacturing of OLEDs [116,126,127,128]. Control of the PEDOT:PSS ratio, the solvents employed or the addition of surfactants to inks, strongly influence the morphology and the electric properties of the final applied materials after solvent evaporation [129].…”
Section: Inkjet Printing Of Light Emitting Devicesmentioning
confidence: 99%
“…If a display is a rigid structure (i.e., the pitch between OLED cells is equal) and the location of the display is known at all times, the printing task could be executed with a constant velocity and a constant drop-on-demand (DOD) print-frequency [17]. Existing research adopting this technique can be found in, e.g., [18] and [19], an overview of inkjet-based micro-manufacturing is given in [20]. However, due to the flexible nature of the display and the absence of a proper fixation system, a designed trajectory is a necessity.…”
Section: B Industrial Inkjet Printingmentioning
confidence: 99%
“…For the printing task, the print-head shoots a polymer droplet, which has a diameter of 50 [ ], at the center of each OLED cell (see Fig. 3 and [19]). In order to execute an accurate printing task, the delay of the printing task itself needs to be taken into account.…”
Section: B Industrial Inkjet Printingmentioning
confidence: 99%